2019
DOI: 10.1016/j.csbj.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

DNA i-Motifs With Guanidino-i-Clamp Residues: The Counterplay Between Kinetics and Thermodynamics and Implications for the Design of pH Sensors

Abstract: I-motif structures, adopted by cytosine-rich DNA strands, have attracted considerable interest as possible regulatory elements in genomes. Applied science exploits the advantages of i -motif stabilization under acidic conditions: i -motif-based pH sensors and other biocompatible nanodevices are being developed. Two key characteristics of i -motifs as core elements of nanodevices, i.e. , their stability under physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Based on mechanisms of polyamine binding to i-motifs, additional research is needed to identify additional ligands with greater affinity by altering the molecular length of the polyamines. Kinetic analysis has shown that the addition of 5′-terminal guanidino-i-clamp ( Tsvetkov et al, 2019 ) or i-clamp ( Tsvetkov et al, 2018 ) can decrease the unfolding rate of synthetic i-motifs, which guarantees the stability of i-motifs. It is also possible to become unstable given the steric hindrance.…”
Section: Types Of I-motifsmentioning
confidence: 99%
“…Based on mechanisms of polyamine binding to i-motifs, additional research is needed to identify additional ligands with greater affinity by altering the molecular length of the polyamines. Kinetic analysis has shown that the addition of 5′-terminal guanidino-i-clamp ( Tsvetkov et al, 2019 ) or i-clamp ( Tsvetkov et al, 2018 ) can decrease the unfolding rate of synthetic i-motifs, which guarantees the stability of i-motifs. It is also possible to become unstable given the steric hindrance.…”
Section: Types Of I-motifsmentioning
confidence: 99%
“…Previously tested approaches to improving iM stability in neutral medium include the incorporation of non-native residues (nucleoside analogues) or extra structural elements (loops) into the iM structure and the usage of cyclopeptide scaffolds. Also, intrinsically (semi)­stable iMs can be found among genomic sequences that contain four long cytosine tracts (C 5+ ) separated by short loops or dC homopolymers following the “4n-1” rule. ,, In contrast to bimodular (iM+hairpin) structures that typically require an additional complementary chain to induce concentration-dependent rearrangements, genomic unimolecular iMs show concentration-independent folding/unfolding. In the recent study, we examined a genomic dC homopolymer ATX labeled with terminal fluorophore and quencher residues.…”
mentioning
confidence: 99%